2015
DOI: 10.1016/j.jnutbio.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 6-month caloric restriction on Cu bound to ceruloplasmin in adult overweight subjects

Abstract: In a randomized clinical trial of calorie restriction (CR), we demonstrated that important cardiovascular disease (CVD) biomarkers were favorably influenced by CR alone and in conjunction with physical exercise. The aim of this study was to examine the effects of CR with or without exercise on Copper bound to Ceruloplasmin (CuCp), a well-known biomarker for CVD, in overweight men and women enrolled in the CALERIE phase 1 study. Forty-six individuals were randomized to one of four groups for 6 months: control: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Finally, two studies, Racette 2006 [ 66 ] and Heilbronn 2006 [ 62 , 68 , 72 ], showed an improvement in insulin sensitivity that was associated with reductions in whole-body fat mass (r = −0.46; p = 0.001), visceral adipose tissue (r = −0.51; p < 0.01) and subcutaneous abdominal adipose tissue (r = −0.32; p < 0.05) [ 62 , 68 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, two studies, Racette 2006 [ 66 ] and Heilbronn 2006 [ 62 , 68 , 72 ], showed an improvement in insulin sensitivity that was associated with reductions in whole-body fat mass (r = −0.46; p = 0.001), visceral adipose tissue (r = −0.51; p < 0.01) and subcutaneous abdominal adipose tissue (r = −0.32; p < 0.05) [ 62 , 68 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, copper-carrying proteins, such as ceruloplasmin, positively correlate with insulin resistance in subjects at increased diabetes risk (Aguilar et al 2013). Lifestyle modifications such as caloric restriction and physical exercise are associated with lower circulating levels of copper bound to ceruloplasmin in people that are overweight (Piacenza et al 2015). Overall, these results show a correlation between higher circulating copper levels and worse blood glucose control.…”
Section: Coppermentioning
confidence: 90%